Perceptions of medical students undergoing cadaveric training - Hassan, Maaroof Tahseen (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Anatomy education is a principal subject within international medical and scientific curricula. Evidence based literature suggests that cadaver dissection is highly effective in establishing and retaining anatomy concepts. This study aimed to examine the perceptions of medical students about socio-cognitive aspects of dissection of human body in the Department of Anatomy at the College of Medicine, Hawler Medical University, Erbil. More specifically, the study tried to find out perceptions and level of satisfaction of medical students with engagement factors that improve positive satisfaction in learning. Methods: This is a descriptive cross-sectional study that included 169 first year medical students in the College of Medicine, Hawler Medical University. A self-administered questionnaire was distributed to the medical students during their practical anatomy sessions in the Department of Anatomy. Results: More than half of the students (55%) felt normal on their first exposure to dissection. Almost around half of the students (48.6%) had increased value for fellow humans following cadaveric training. More than 95% of them thought that improvement is needed in the cadaveric training. About 40% of the respondents had a good adaptation to cadaveric training. Conclusion: The traditional dissection laboratory must remain the center for teaching and learning anatomy. It is necessary to examine the curriculum and the mode of teaching. Factors that improve positive perceptions and in learning, like helpful environment and adequate dissection instructors should be thoroughly engaged in the training of our future doctors.